2011
DOI: 10.1021/jz201373e
|View full text |Cite
|
Sign up to set email alerts
|

π-Hydrogen Bonding in Liquid Water

Abstract: Experimental MethodsRaman Spectral Measurements: Raman spectra were obtained using a home-built, micro-Raman system similar to that used in previous studies (1). The system used in the present studies includes an Ar-Ion laser source (514.5nm, ~ 50 mW power at the sample) and a thermoelectrically cooled CCD detector (Princeton Instruments Inc., Pixis 400, 1340x400 pixel) mounted to a 300 mm focal length imaging spectrograph (SpectraPro300i, Acton Research Inc.), with a 300 g/mm grating, such that the dispersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
184
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(201 citation statements)
references
References 36 publications
9
184
0
8
Order By: Relevance
“…(69) In combination with computational studies, their results revealed the OH–π bond is ∼20% weaker and more flexible than bulk HBs. Furthermore, their results suggest that dangling HBs are more entropically favored but less enthalpically favored than water-water HBs.…”
Section: Zero Curvaturementioning
confidence: 96%
“…(69) In combination with computational studies, their results revealed the OH–π bond is ∼20% weaker and more flexible than bulk HBs. Furthermore, their results suggest that dangling HBs are more entropically favored but less enthalpically favored than water-water HBs.…”
Section: Zero Curvaturementioning
confidence: 96%
“…15 A conversão de uma ligação de hidrogênio água-água (Figura 5a) em uma ligação de hidrogênio água-benzeno (nuvem π) (Figura 5b) é favorecida pela entropia (∆S > 0), mas desfavorecida pela entalpia (DH > 0). Apesar de incomum, este tipo de ligação pode ter relevância em processos biológicos.…”
Section: Hidrocarbonetosunclassified
“…Apesar de incomum, este tipo de ligação pode ter relevância em processos biológicos. 15 É importante ressaltar que a interação eletrons π -hidrogênio não afeta a solubilidade do benzeno em água (0,07 g/100 g de H 2 O a 23 o C), 4 portanto, o seu comportamento é o apresentado, em geral, pelos hidrocarbonetos: pouco solúveis em água e solúveis em solventes apolares.…”
Section: Hidrocarbonetosunclassified
“…This conformer was found for the benzene-water heterodimer in previous experiments in the gas phase 33 and in the liquid phase. 34 Using DFT calculations, we found a structure in which one hydrogen is H bonded to the p electron network and the second hydrogen atom of the water molecule is bonded to the nitrogen. However, the expected field dependency for the D-O stretch for the band at 2776.2 cm À1 predicted for this structure does not match the experimental results (VTMA 46.11).…”
Section: Dependency Of the Bands On Applying A DC Electric Fieldmentioning
confidence: 99%